2020
DOI: 10.1002/anie.202008736
|View full text |Cite
|
Sign up to set email alerts
|

Room‐Temperature Phosphorescence Invoked Through Norbornyl‐Driven Intermolecular Interaction Intensification with Anomalous Reversible Solid‐State Photochromism

Abstract: Herein, norbornyl (NB), ab ulkya nnular nonconjugated spacer,i sm elded into p systems to construct two groups of ladder-type room-temperature phosphorescence (RTP) luminogens.T he effect of the NB on p-p interactions, packing modes and RTP performance is explored systematically.The experimental and computational results demonstrate the versatility of NB in reducing p-p distances and synergistically intensifying the intermolecular interactions,w hich not only induces intersystem crossing from S 1 to T n but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 72 publications
1
37
0
Order By: Relevance
“…In addition, the applications of the dual‐emissive compounds, which include quantitative imaging of tumour hypoxia, in vivo camera wound imaging, RGB‐channel‐based camera imaging, ratiometric sensing of oxygen and temperature, emission‐lifetime‐based data encryption and decryption, white‐light‐emission, and OLED, are also presented. Meanwhile, several dual‐emissive compounds that cannot be classified into the categories exist, that include (pinacolatoboryl)arenes, [63] boron cluster, [64] 1‐benzyl‐4,4′‐bipyridinium, [65] 2,5‐disiloxy‐1,4‐bis(diarylphosphinyl)benzene, [45] difluorotetrakis(arylthiol)benzene, [66] brominated fluorenes, [67] naphthalimides, [68] norbornane‐annulated arenes, [69] tetrakis(aryloxy)phthalonitriles, [2c] N ‐alkyl‐ and N ‐benzoylcarbazoles, [70] N , N ′‐di(1‐naphthyl)‐ N , N ′‐di‐phenyl‐(1,1‐biphenyl)‐4,4‐diamine, [71] polyimides, [72] N ‐(4‐trifluoromethylphenyl)‐4‐bromophthalimide, [73] di(phenothiazinyl)naphthalene, [3b] di(phenothiazinyl)dibenzothiophenes, [74] and three‐component crystals consisting of 5,5′‐(ethyne‐1,2‐diyl)‐bis(2‐pyridin‐3‐yl‐isoindoline‐1,3‐dione), tris(pentafluorophenyl)borane, and simple benzenes [75] . We hope that this article will contribute to the advancement of fluorescence–phosphorescence dual‐emissive materials and their applications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the applications of the dual‐emissive compounds, which include quantitative imaging of tumour hypoxia, in vivo camera wound imaging, RGB‐channel‐based camera imaging, ratiometric sensing of oxygen and temperature, emission‐lifetime‐based data encryption and decryption, white‐light‐emission, and OLED, are also presented. Meanwhile, several dual‐emissive compounds that cannot be classified into the categories exist, that include (pinacolatoboryl)arenes, [63] boron cluster, [64] 1‐benzyl‐4,4′‐bipyridinium, [65] 2,5‐disiloxy‐1,4‐bis(diarylphosphinyl)benzene, [45] difluorotetrakis(arylthiol)benzene, [66] brominated fluorenes, [67] naphthalimides, [68] norbornane‐annulated arenes, [69] tetrakis(aryloxy)phthalonitriles, [2c] N ‐alkyl‐ and N ‐benzoylcarbazoles, [70] N , N ′‐di(1‐naphthyl)‐ N , N ′‐di‐phenyl‐(1,1‐biphenyl)‐4,4‐diamine, [71] polyimides, [72] N ‐(4‐trifluoromethylphenyl)‐4‐bromophthalimide, [73] di(phenothiazinyl)naphthalene, [3b] di(phenothiazinyl)dibenzothiophenes, [74] and three‐component crystals consisting of 5,5′‐(ethyne‐1,2‐diyl)‐bis(2‐pyridin‐3‐yl‐isoindoline‐1,3‐dione), tris(pentafluorophenyl)borane, and simple benzenes [75] . We hope that this article will contribute to the advancement of fluorescence–phosphorescence dual‐emissive materials and their applications.…”
Section: Discussionmentioning
confidence: 99%
“…reported two groups of ladder‐type organic phosphors ( Figure a). [ 53 ] In group B, they utilized the bulky norbornyl (NB) moiety to separate N ‐methyl phthalimide groups, achieving persistent RTP for which the phosphorescence lifetime can reach 357.1 ms with quantum yields up to a relatively high value of 2% (Figure 4a). By analyzing the crystal structure, they found that a parallel stacking alignment reduces the p – p distances which generate stronger hydrogen to oxygen and p interactions between molecules (Figure 4b).…”
Section: Single Component Rtp Systemsmentioning
confidence: 99%
“…Materials with room temperature phosphorescence (RTP) have shown application prospects in the fields of information encryption, [1][2][3][4][5] dynamic anti-counterfeiting, [6][7][8][9][10] chemical sensing, [11] and biological imaging. [12][13][14] The RTP phenomenon comes from the process that triplet excited states (T 1 ) move back to the reaction procedure.…”
Section: Introductionmentioning
confidence: 99%